ChemInform Abstract: Synthesis, Magnetism, and Electrochemistry of the Ni14‐ and Ni5‐ Containing Heteropolytungstates [Ni14(OH)6(H2O)10 (HPO4)4 (P2W15O56)4]34‐ and [Ni5(OH)4(H2O)4 (β‐GeW9O34) (β‐GeW8O30(OH))]13‐. Issue 40 (12th September 2013) - Ibrahim, Masooma; Xiang, Yixian; Bassil, Bassem S.; Lan, Yanhua; Powell, Annie K.; de Oliveira, Pedro; Keita, Bineta; Kortz, Ulrich
Abstract The two new compounds (IV) and (VII) are synthesized and characterized by single crystal XRD, IR spectroscopy, cyclic voltammetry, and magnetic measurements.